PENINGKATAN KEMAMPUAN SOFT SKILLS MAHASISWA BIOLOGI FKIP UNIVERSITAS RIAU PADA MATAKULIAH GENETIKA DAN EVOLUSI MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) - Darmawati '; Imam Mahadi (Biogenesis, 2014)
This study was conducted to determine the increase in soft skills FKIP Riau University Biology students through PBL learning model. Research subjects are biology students 4th semester (four) year 2012/2013, amounting to 19 people. This type of research is action research. The research instrument is a learning device (Syllabus, SAP, LKM, Textbook), while collecting data by observation sheet. Parameters of soft skills is a creative research, analysis, communication, problem solving, management, independent and work together. Data were analyzed descriptively. The results showed that the average soft skills of students in the first cycle 71.68% (excellent) increased to 80.64% (excellent) on the second cycle. Thus the application of PBL models can improve the soft skills of students at the University of Riau FKIP Biology course Genetics and Evolution.Keywords: Genetics and Evolution, soft skills Ability, Problem Based Learning (PBL)